A Review of Rare Earth Mineral Processing Technology - Liyananadirah, Mat Suli; Wan Hanisah, Wan Ibrahim; Badhrulhisham, Abdul Aziz; Mohd Rizauddin, Deraman; Nurul Ain, Ismail (Bangladesh University of Engineering and Technology, 2017)
The recent technological advancement has made the rare earth elements (REEs) more significant and they in turn have facilitated the culmination of more new technological applications owing to their unique physical and chemical properties. In this regard, renewable energy applications such as wind turbine and hybrid cars testify to the increasing demands on permanent magnet in the future. Considering such increasing demands on REEs, it is felt necessary to identify alternative producers of REEs outside of China as one of the measures to create a fair competition and control the price on the market. It is worth highlighting that the separation of rare earth can be both complex and challenging owing to similar properties which are shared by them. The purpose of this paper is to comprehensively review and summarize the rare earth processing routes, the mostly employed rare earth separation methods, supply and demand of rare earth around the world and some possible scenarios in rare earth market. This review has critically looked into a few authors recent reviews on six major processes of rare earth processing steps and each step is considered as important to produce both high quality and better quantity of REEs.